2020
DOI: 10.21467/ajss.7.1.138-144
|View full text |Cite
|
Sign up to set email alerts
|

Growing up in a Single Parent Family; A Determining factor of Adolescent’s Well-being

Abstract: Family is the backbone of all children and children are supposed to grow in a family setting where both mother and father plays their respective roles in providing them a sense of security and stability but when it is done single handedly it becomes quite difficult to perform up to the expectations.  In recent years, there has been a sudden rise in the phenomenon of single parent families in India due to multiple factors including the influences from western society. The present article is an attempt to review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…They also tend to develop the ability to manage their expectations and disappointments better and feel motivated to share their burden. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also tend to develop the ability to manage their expectations and disappointments better and feel motivated to share their burden. [ 32 ]…”
Section: Resultsmentioning
confidence: 99%
“…Parents perform multiple culturally, socially, and biologically determined roles to ensure the development and well-being of their children. [ 1 ] Parental roles are mainly divided among both parents in dual-parent families (also known as intact families). Still, a breakdown in the family may lead to a different family structure altogether called a single-parent family.…”
Section: Introductionmentioning
confidence: 99%
“…The study also found that no statistically significant difference in AA existed between students in singlemother vs. dual-parent families after controlling for FSES, demonstrating the latter's importance to AA. Previous studies have shown that single-mother families are often poor and vulnerable due to the division of family property, labor market discrimination, shrinking social support, and an inadequate social security system (Gupta and Kashyap, 2020;Stack and Meredith, 2018;Damaske et al, 2017;Wu et al, 2016). Meanwhile, singleparent families in economic poverty cannot provide high-quality educational resources for their children, thereby affecting the latter's academic success (Zhang, 2020a(Zhang, , 2020b.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a mother or father disrupts the natural composition of the family and disturbs the natural state within it (Grandić & Dedaj, 2016, p. 143). Family is the fundamental social group, comprising of parents and their children (Gupta & Kashyap, 2020). From a pedagogical point of view, a functional family is a family that provides children with a proper physical, mental and emotional development (Grandić & Dedaj, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Family is the backbone of all children and children are supposed to grow in a family setting where both parents play their respective roles in providing them a sense of security and stability (Gupta & Kashyap, 2020). Life in a harmonious primary family is the right that belongs to all children (Čirjak, 2002).…”
Section: Introductionmentioning
confidence: 99%